2007
DOI: 10.1109/iembs.2007.4353144
|View full text |Cite
|
Sign up to set email alerts
|

Design of Novel Assessment Techniques for Opioid Dependent Patients

Abstract: Assessment of opioid dependent patients in a replacement program has traditionally relied on conventional methods such as urine testing or face to face examination with a physician. We are introducing new assessment techniques based on pupillometry, reaction time and slurring of speech. The pupillometry test uses a webcam, controlled lighting and customized software to measure pupil parameters. The reaction time test uses a push-button to detect time to respond to a visual stimulus. The slurred speech test inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…[ 23 ] However, the finding of our study with respect to reaction times being comparable among subjects of opioid use disorder and controls is not in accordance with other studies reported in literature. [ 24 25 ] These cognitive deficits among subjects of substance use disorders have been reported to be similar to individuals with damage to the prefrontal cortex, an area that has the ability to organize thoughts, prioritize tasks, manage time, and make decisions, including exerting control over substance. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] However, the finding of our study with respect to reaction times being comparable among subjects of opioid use disorder and controls is not in accordance with other studies reported in literature. [ 24 25 ] These cognitive deficits among subjects of substance use disorders have been reported to be similar to individuals with damage to the prefrontal cortex, an area that has the ability to organize thoughts, prioritize tasks, manage time, and make decisions, including exerting control over substance. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…Nele, o eyetraker comercial ISCAN modelo RK-426, Cambridge, MA foi integrado a um computador pessoal para estimulação visual/auditiva com o monitoramento simultâneo do diâmetro da pupila. Já em 2007 num estudo para determinação do estado de sedação do paciente, Patil et al (2007) integraram, em um único dispositivo, mecanismos para a estimulação visual, a monitoração da fala e da dinâmica da pupila.…”
Section: Introductionunclassified